A Five-Year Stability Study of Controlled-Release Diltiazem Hydrochloride Tablets Based on Poly(Ethylene Oxide) - Laila H. Emara, Ahmed A. El-Ashmawy, Nesrin F. Taha (Journal of Applied Pharmaceutical Science, 2015)
The aim of this study is to investigative the stability of poly(ethylene oxide) (PEO) matrix tablets containing diltiazem hydrochloride (DTZ) after five-year storage at room temperature. DTZ matrix tablets containing different molecular weights (MW) of PEO and electrolytes (sodium carbonate anhydrous Na2CO3, potassium chloride KCl and pentasodium tripolyphosphate anhydrous PSTPP) were prepared. The fresh and stored tablets were evaluated by DTZ content, in vitro drug release rates and kinetics as well as DSC. All the PEO’s matrix tablets showed no significant changes in release rate, kinetics and drug content. The release rates of DTZ following five-year storage were slightly increased as the MW of PEO increased from 900,000 to 8,000,000. Also, it was clear that the addition of electrolyte drastically slowed the release rates of DTZ from fresh and stored tablets. DSC thermograms and similarity factor (ƒ2) depicted good system stability for all stored tablets. This is the first five-year long-term stability study reported concerning DTZ/PEO matrix tablets with different MW, which proved its stability for several years. This study might throw light on the dramatic difference observed between this study and the reported data of accelerated stability testing under stress conditions found in the literature.
Keywords: Polyethylene oxide (PEO), Diltiazem hydrochloride, Five-year long-term stability, Electrolyte, Gel-matrix tablets, Release kinetics.